IN SITU INVESTIGATION OF GALENA DISSOLUTION IN OXYGEN SATURATED SOLUTION: EVOLUTION OF SURFACE FEATURES AND KINETIC RATE - De Giudici G.; Zuddas P. (My University, 2001)
In this work, an original Atomic Force Microscopy (AFM) investigation was carried out combining in situ microtopography measurements with solution chemistry. The dissolution of galena (PbS) surface in acidic (HCl, pH = 1) and oxygen saturated solution was investigated in an AFM liquid cell at room temperature over 45 h. In this apparatus, solution circulates into the flow-through reactor at high-flow rate and is periodically sampled for chemical analysis. In the first hours of microtopography measurement square etch pits delimited by steps of minimal depth of 1 nm nucleate and growth attaining a maximal depth of 80 nm. After this short stage, surface features evolve by formation of widespread protrusions 1 to 3 nm high and homogeneously distributed, while nucleation and growth of new etch pits is inhibited, and large rough terraces delimited by macrosteps 50 to 100 nm high are formed by dissolution. The solution interacting with galena surface is strongly undersaturated with respect to both galena and anglesite (PbSO4), namely solution saturation state for these minerals decreases during the experiment by more than two order of magnitude, and dissolution rate was then derived from lead concentration in solution. During the duration of the experiment, dissolution rates decrease by more than one order of magnitude attaining a final value of 4.5 +/- 0.5 x 10-8 mol m-2 sec-1. Other dissolution experiments performed using different mineral grains confirmed the reproducibility of the galena surface evolution process. However, protrusion observed at lower hydrogen ion activity (pH = 3) showed a rounded shape. From thermodynamic and XPS data in the literature, we predicted that nanometric protrusions are composed of native sulphur, an intermediate and slowly dissolving phase that, in turn, react with oxygen to dissolve and migrate towards bulk solution in a more oxidised state (eg. asSO42-, S2O32-, etc.).We interpreted that the protrusion dissolution reaction represents the step limiting the rate of the overall dissolution reaction, and the evolution of the rate regime is a transitory stage due to the continuous increase in the thickness of the altered layer that coats the surface. Finally, this nanoscale detailed description of galena dissolution process is relevant in terms of both reaction mechanisms and computational modelling of metal sulphide oxidation processes.